Corrosion Inhibitor for Printed Circuit Board using Papaya Leaves Extract - Mohd Radzuan, Nurmira Batrisyia; Embong, Zaidi; Jafery, Khawarizmi; Rahim, Siti Maisarah; Mohd Basir, Mohd Sidiq (Enhanced Knowledge in Sciences and Technology, 2025)
This study explores the potential of papaya leaf extract (PLE) as an eco-friendly corrosion inhibitor for copper in printed circuit boards (PCBs) immersed in sodium chloride (NaCl) solutions. A systematic approach was employed, starting with the preparation of PLE through extraction using 70% ethanol at 45°C for 2.5 hours. The efficiency of PLE as a corrosion inhibitor was evaluated by immersing copper PCBs in 1 M NaCl solutions with varying ratios of PLE (100% NaCl, 90% NaCl and 10% PLE, 70% NaCl and 30% PLE, and 50% NaCl and 50% PLE). Fourier Transform Infrared (FTIR) spectroscopy identified key functional groups in PLE, including O-H (~3400 cm⁻¹), C-H (~2900 cm⁻¹), C=O (~1700 cm⁻¹), and C=C aromatic vibrations (1600–1500 cm⁻¹), as well as C-O or C-N stretching (~1200–1000 cm⁻¹), indicative of polyphenols, flavonoids, and tannins, which adsorb onto the copper surface to inhibit corrosion. Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDX) showed a significant increase in copper content and a decrease in oxygen concentration with higher PLE concentrations and it also reduces surface roughness, minimizes pitting. The copper atomic percentage increased from 47.8% in pure NaCl (100% NaCl) to 84.0% in the solution containing 50% NaCl : 50% PLE, while oxygen content decreased from 26.2% to 10.8%. Electrochemical studies, including Tafel polarization and Nyquist impedance plots, demonstrated that PLE acts as a mixed-type inhibitor, reducing anodic and cathodic reactions and significantly enhancing charge transfer resistance. At the ratio mixture of 50% NaCl: 50% PLE, the copper surface exhibited maximum protection, with a dense and uniform inhibitor layer. These findings highlight the potential of PLE as an eco-friendly and sustainable corrosion inhibitor for copper in harsh environments.